Arpin downregulation is associated with poor prognosis in pancreatic ductal adenocarcinoma. Issue 5 (May 2019) - Zhang, Shi-Rong; Li, Hao; Wang, Wen-Quan; Jin, Wei; Xu, Jin-Zhi; Xu, Hua-Xiang; Wu, Chun-Tao; Gao, He-Li; Li, Shuo; Li, Tian-Jiao; Zhang, Wu-Hu; Xu, Shuai-Shuai; et al.
Abstract: Introduction: Arpin (Arp2/3 complex inhibitor), a novel protein found in 2013, plays a pivotal role in cell motility and migration. However, the prognostic value of Arpin in pancreatic ductal adenocarcinoma (PDAC) remains unknown. Materials and methods: We analyzed the gene expression of ARPIN using the GEO dataset (GSE71989) and validated the results by immunohistochemistry (IHC) and Western blot in our clinical database. Tissue microarray specimens from 214 patients who underwent curative pancreatectomy for PDAC were used. The tumors that expressed high and low levels of Arpin were compared with patient outcome using Kaplan-Meier curves and the multivariate Cox proportional hazard regression model. IHC was then used in 43 paired primary tumor tissues and metastasis tissues to detect the expression of Arpin. Results: Arpin had low expression in the tumor tissue compared with the paracancerous tissue in PDAC. Patients with low intratumoral Arpin expression had worse overall survival (OS) and recurrence-free survival (RFS) than patients with high expression in the training set ( p  < 0.001, p  < 0.001) and validation set ( p  < 0.001, p  < 0.001). The multivariate analysis revealed that the 8th edition TNM stage and Arpin expression were independent prognostic factors associated with OS and RFS in the training and validation sets, respectively. Arpin had lower expression in the metastasis tissues than in the primary tumors of patients with PDAC ( p  = 0.048). Conclusion: The Arpin level is an independent prognostic factor that can be a potential predictor to aid in the management of PDAC.